Mayor of Kingstown. Season one [videorecording (DVD)] - Sheridan, Taylor; Dillon, Hugh, 1963- (Paramount, 2022)
From Academy Award nominee Taylor Sheridan, co-creator of Yellowstone, and Hugh Dillon, it follows the McLusky family-power brokers in Kingstown, Michigan, where the business of incarceration is the only thriving industry. Tackling themes of systemic racism, corruption and inequality, the series provides a stark look at their attempt to bring order and justice to a town that has neither.